Palaeoglaciation in the Low Latitude, Low Elevation Tropical Andes, Northern Peru - Lee, Ethan; Ross, Neil; Henderson, Andrew C. G.; Russell, Andrew J.; Jamieson, Stewart S. R.; Fabel, Derek (Frontiers in Earth Science, 2022)
Characterising glaciological change within the tropical Andes is important because tropical glaciers are sensitive to climate change. Our understanding of glacier dynamics and how tropical glaciers respond to global climate perturbations is poorly constrained. Past studies in the tropical Andes have focused on locations where glaciers are still present or recently vacated cirques at high elevations. Few studies focused on lower elevation localities because it was assumed glaciers did not exist or were not as extensive. We present the first geomorphological evidence for past glaciations of the Lagunas de Las Huaringas, northern Peru, at elevations of 3900-2600 m a.s.l. Mapping was conducted using remotely-sensed optical imagery and a newly created high-resolution (~2.5 m) digital elevation model. The area has abundant evidence for glaciation, including moraines, glacial cirques, hummocky terrain, glacial lineations and ice-sculpted bedrock. Two potential models for glaciation are hypothesised: (i) plateau-fed ice cap, or (ii) valley glaciation. Assuming glaciers reached their maximum extent at the local Last Glacial Maximum (LLGM), 23.5 ± 0.5 and 21.2 ± 0.8 ka, a maximum glacial area of 75.6km2 and mean equilibrium line altitude (ELA) of 3422 ± 30 m, indicating an ELA change of -1178 ± 10 m compared to modern snowline elevation. There is an east to west ELA elevation gradient, lower in the east and higher in the west, in-line with modern day transfer of moisture. Applying lapse rates between 5.5°C/km - 7.5°C/km provides a LLGM temperature cooling of between 6.5-8.8°C compared to present. These values are comparable to upper estimates from other studies within the northern tropical Andes and from ice-core reconstructions. However, contrast with some valley glacier estimates. This mapping of glacial geomorphology within the Lagunas de las Huaringas, for the first time, presents extensive glaciation in low elevation region of northern Peru with implications for our understanding of past climate in the sub-tropics. Observations and reconstructions support a valley glaciation. Further work is required to constrain the timing of the glaciations, with evidence younger than the LLGM, up-valley of maximum glacier extents. While numerical modelling will enable an understanding of the controls on glaciation within the region.